INTERNALISASI NILAI-NILAI PANCASILA DI PERGURUAN TINGGI - Dwi Riyanti; Danang Prasetyo (Citizenship Jurnal Pancasila dan Kewarganegaraan, 2019)
This study aims to determine the process of internalizing Pancasila values in higher education. The reason for this research is because over time Pancasila among the younger generation who are often called millennials is fading. This research is a descriptive study using qualitative approach. This research was conducted at Ahmad Dahlan University aimed at Pancasila courses by determining research subjects using puposive sampling techniques. Data collection techniques using interviews and documentation and using data analysis techniques using triangulation of sources. The results of this study are that the Pancasila course is more effective using a contextual approach by developing academic potential, preparing to live side by side in the community, and building a living culture according to Pancasila values. The way to internalize Pancasila to students is by: (1) providing knowledge about Pancasila as a state ideology so that students refuse other ideologies besides Pancasila. (2) provide exemplary examples such as discipline, tolerance, and religious attitude. (3) visit to the Pancasila Village in the City of Yogyakarta to learn the success of civilizing life based on the value of Pancasila, raising funds for social services. Therefore, students increasingly understand and are able to practice the precepts of Pancasila.